Analisis Beban Kerja dan Pengaruhnya Terhadap Kelelahan Kerja Serta Gangguan Muskuloskeletal pada CV XYZ - Sarifuddin, Ahmad; Sajiyo, Sajiyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the physical and mental workload and their influence on work fatigue and musculoskeletal disorders among employees at CV XYZ, a metal fabrication company characterized by high operational intensity. Data were collected through direct observation, interviews, and questionnaires, including physical workload measurement using the Cardiovascular Load (CVL) method, mental workload assessment using the NASA-TLX method, work fatigue evaluation using a 30-item fatigue questionnaire, and musculoskeletal disorder assessment using the Nordic Body Map (NBM). The results showed that the average physical workload was categorized as moderate, with a CVL value of 53.31%. Meanwhile, the mental workload was found to be very high, with an average score of 82. The level of work fatigue after performing tasks reached an average score of 81, classified as high, indicating significant fatigue accumulation among workers. Additionally, musculoskeletal complaints yielded an average score of 34.45, categorized as moderate, with two workers experiencing high-risk symptoms. These findings indicate that employees exposed to substantial physical and mental demands that contribute to increased fatigue and musculoskeletal complaints. Therefore, ergonomic interventions, workload adjustment, and improvements in work conditions are essential to reduce fatigue levels and enhance worker well-being and productivity.